The Effect of Giving Stretching Exercise To Decrease The Pain in Patients with Iskhialgia in Latu Usadha Nursing Care Clinic - Putu Aristiana Santi (Coping: Community of Publishing in Nursing, 2013)
Pain is one of the main complaints of clients that drives someone to come to the health care. Pain that often arises is musculoscletal pain and one of them is iskhialgia. Iskhialgia is manifestation of lower back pain that caused due to a nerve ischiadicus clamping. This research aimed to know the effect of giving stretching exercise to decrease the pain in patients with iskhialgia. This research were pre-experimental research design by using one group pre-post test design. The number of samples were 19 respondents in nonprobability with concecutive sampling. Data analysis techniques which used to test the hypothesis that were Paired Sample T-Test with significancy level of 5% (0.05). The results of research showed the average of pain level before giving stretching exercise were 4,89 and after were 3,21. P-value = 0,000 its means that p <0.05 so that Ho is rejected, then it can be stated that there was effect of giving stretching exercise to decrease the pain in patients with iskhialgia in Latu Usadha Nursing Care Clinic Abiansemal Badung. Based on the results of this research will be suggested to the nurse in order to use stretching exercise as an non farmacologic techniques in the treatment of pain in iskhialgia. the next researchers should use control group in order to make the result more representative.